UNDERSTANDING THE PROCESS OF RADICALIZATION: AN INTERVIEW ANALYSIS THROUGH FATHALI MOGHADDAM'S STAIRCASE MODEL - Tiara Amima Putri Dewi; Sapto Priyanto; Imam Subandi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to understand the radicalization process of former terrorist convicts in Indonesia through the framework of Fathali Moghaddam's Staircase Model. Unlike previous studies that were primarily conceptual or based on secondary data, this study utilizes semi-structured interviews with a former terrorist convict, analyzed through thematic analysis to explore the psychological, social, and religious dynamics at each stage of radicalization. The results indicate that radicalization is not solely triggered by structural factors but is also influenced by relational pressures (family and religious study communities), ideological justification through deviant religious interpretations, and the role of social media in accelerating the strengthening of radical identities. These findings confirm the relevance of the Staircase Model in the local context, while highlighting its limitations as it does not fully accommodate relational and digital variables. Thus, this study contributes to the development of theoretical understanding of radicalization and offers implications for deradicalization policies that emphasize early family-based intervention, moderate religious education, and digital literacy to prevent extremist propaganda.